Comparative investigation of IFN-γ-producing T cells in chickens and turkeys following vaccination and infection with the extracellular parasite Histomonas meleagridis. (March 2021) - Lagler, Julia; Schmidt, Selma; Mitra, Taniya; Stadler, Maria; Patricia Wernsdorf,; Grafl, Beatrice; Hatfaludi, Tamas; Hess, Michael; Gerner, Wilhelm; Liebhart, Dieter
Abstract: The re-emerging disease histomonosis is caused by the protozoan parasite Histomonas meleagridis that affects chickens and turkeys. Previously, protection by vaccination with in vitro attenuated H. meleagridis has been demonstrated and an involvement of T cells, potentially by IFN-γ production, was hypothesized. However, comparative studies between chickens and turkeys on H. meleagridis -specific T cells were not conducted yet. This work investigated IFN-γ production within CD4 +, CD8α + and TCRγδ + (chicken) or CD3ε + CD4 − CD8α − (turkey) T cells of spleen and liver from vaccinated and/or infected birds using clonal cultures of a monoxenic H. meleagridis strain. In infected chickens, re-stimulated splenocytes showed a significant increase of IFN-γ + CD4 + T cells. Contrariwise, significant increments of IFN-γ-producing cells within all major T-cell subsets of the spleen and liver were found for vaccinated/infected turkeys. This indicates that the vaccine in turkeys causes more intense systemic immune responses whereas in chickens protection might be mainly driven by local immunity. Highlights: Establishing intracellular cytokine staining for IFN-γ in turkey lymphocytes. Data suggest Th1-dominated immune responses following infection with H. meleagridis. Involvement of different IFN-γ-producing T-cell subsets comparing chickens and turkeys. Stronger systemic T-cell immune response in turkeys following vaccination + infection.